2002
DOI: 10.1080/09658210143000326
|View full text |Cite
|
Sign up to set email alerts
|

Source monitoring in a generative task

Abstract: Following exposure to experimenter-provided examples of space creatures, people tend to conform to the features contained in the examples when creating their own novel space creatures. In three experiments, we manipulated factors known to affect source-monitoring accuracy to determine how these manipulations would influence conformity to experimenter-provided examples. In Experiment 1 we altered people's cognitive agenda by means of the instructions given before the drawing task. In Experiment 2 we examined ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Interestingly, when the activation of common knowledge was reinforced by the presentation of possible solutions belonging to the fixation path, participants proposed fewer, less original solutions. This finding is in agreement with several previous works, and confirms that recently activated knowledge can strongly constrain the ability to generate creative solutions (Jansson & Smith, 1991;Landau & Leynes, 2004;Landau et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, when the activation of common knowledge was reinforced by the presentation of possible solutions belonging to the fixation path, participants proposed fewer, less original solutions. This finding is in agreement with several previous works, and confirms that recently activated knowledge can strongly constrain the ability to generate creative solutions (Jansson & Smith, 1991;Landau & Leynes, 2004;Landau et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
“…Two independent experimenters noted whether the subjects' drawings contained any of the previously viewed elements. The results showed that participants tended to incorporate these elements into their own drawings, despite an explicit warning to avoid replicating features given in the examples (see also Jansson & Smith, 1991;Landau & Leynes, 2004;Landau, Thomas, Thelen, & Chang, 2002).…”
mentioning
confidence: 99%
“…Stronger admonitions came from Smith et al (1993), who told their participants that the examples "restrict people's creativity" and to "please generate ideas as different as possible from the examples given" (p. 843). Landau, Thomas, Thelen, and Chang (2002) told participants in one condition not to copy the examples and "that a plagiarism expert would be reviewing their creatures to determine if they had used features from the examples" (p. 190). Only the last set of directions resulted in a substantial reduction in conformity.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…Elsewhere, we have argued that people conform to experimenter-provided examples because it is difficult for them to avoid using certain types of information when engaged in the creative process (e.g., Landau, et al, 2002;Marsh, et al, 1996;. As people create novel entities, details of the examples come to mind when they are selecting features for their novel inventions.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…Thus, exposure to psychology course material is not a panacea for correcting inaccurate beliefs. When people engage these extended retrieval processes, they are less likely to commit a multitude of memory errors (e.g., Landau, Thomas, Thelen, & Chang, 2002;Marsh, Landau, & Hicks, 1997;Multhaup, 1995). When people engage these extended retrieval processes, they are less likely to commit a multitude of memory errors (e.g., Landau, Thomas, Thelen, & Chang, 2002;Marsh, Landau, & Hicks, 1997;Multhaup, 1995).…”
Section: York College Of Pennsylvaniamentioning
confidence: 99%